Methods to Access 2-aminobenzimidazoles of Medicinal Importance - Cruz, Alejandro; Martínez, Itzia I. Padilla; Ramos-Organillo, Angel A. (Current Organic Chemistry, 2019)
Benzimidazole (BI) and derivatives are interesting because several of these compounds have been found to have a diversity of biological activities with clinical applications. In view of their importance, the synthesis of BI and its derivatives is still considered as a challenge for synthetic chemists. Examples of compounds used in medicinal chemistry containing BI, as important nucleus, are Astemizole (antihistaminic), Omeprazole (antiulcerative) and Rabendazole (fungicide), some of these compounds have the 2- aminobenzimidazole (2ABI) as base nucleus. The structure of 2ABI derivatives contains a cyclic guanidine moiety, which is interesting because of its free lone pairs, labile hydrogen atoms and planar delocalized structure. The delocalized 10-π electron system and the extension of the electron conjugation with the exocyclic amino group, in 2ABI, making these heterocycles to have amphoteric character. The 2ABI has been used as building blocks for the synthesis of several BI derivatives as medicinally important molecules. On these bases, herein, we present a bibliographic review concerning the recent methodologies used in the synthesis of 2ABIs, including the substituted ones.
Keywords: 2-mercaptobenzimidazoles